Air Quality Analysis of SO2, NO2 and CO in Palembang City - Shelly Nofri; Muhammad Faizal; Risfidian Mohadi (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2017)
Population activity which tends to centralized in certain area cause decrease in air quality due to exhaust gas from transportation vehicle. From 2011-2014, Palembang city transport growth 3-5% per year comprise of passenger transportation, buses, truck, motorcycle and special vehicle. The increase of vehicle in Palembang gave the city air pollution potential. Transportation is the main source of air pollution in big city with 70% contribution. Exhaust gas from transport activity consist of 60% CO and 15% incomplete combustion of hydrocarbon such as NOx and Sox. The aim of research is to analyzed air quality in Palembang city. Samples were taken and subject to analysis for SO2, NO2 and CO. Sample location were determined by using purposive sampling. Location was chosen by means of traffic density at least for one hour and took place at Charitas crossroads, Patal intersection, Mesjid Agung circle, Lemabang crossroad and Plaju intersection. Result of analysis showed SO2 level is at range 112-208 mg/Nm3/hour. NO2 level between 45-227 mg/Nm3/hour and CO at range 12.595-18.320 mg/Nm3/hour. All parameter of air quality obtained are below threshold value defined by government regulation (GR) on air quality No 41 year 1999.